Pendampingan Penyusunan Laporan Keuangan Berbasis SAK-EMKM dengan Software Accurate Online - Novie Astuti Setianingsih astuti; Wiwiek Kusumaning Asmoro; Atik Tri Andari (Jurnal SOLMA, 2021)
Paving UMKM in Tarokan only record purchases and income manually without adjusting fixed assets and financial reports. Based on these weaknesses, the authors are interested in processing business transaction data for UMKM Paving in Tarokan to produce a financial report that is more precise, easy, fast and accurate so as to improve the quality of financial reports. The purpose of this service is to: 1) Provide more knowledge in making reports finance based on SAK EMKM using accurate software; 2) Introducing online accurate software; 3) Provide assistance in making financial statements with accurate online software. This assistance was carried out at the Paving UMKM in Tarokan, Kalirong Village, Kediri Regency. It will be held on 5 - 30 October 2020. The methods used are the lecture method, the question and answer method and the mentoring method (this method provides assistance in making financial reports for UMKM owners Paving at Tarokan, Kalirong Village, Kediri Regency using the Accurate Online application). Accurate Online software can produce financial reports in a relatively fast, precise, easy and accurate manner according to owner's needs.